Construction Research Congress 2012 2012
DOI: 10.1061/9780784412329.122
|View full text |Cite
|
Sign up to set email alerts
|

Creating 3D Web-Based Game Environment Using BIM Models for Virtual On-Site Visiting of Building HVAC Systems

Abstract: A web-based 3D game project was presented in this paper to demonstrate the process of using building information modeling (BIM) to create an interactive 3D on-line 'Green' training environment. The system architecture, the implementation process and major components of this virtual training environment were discussed. Existing studies on BIM-based collaborations mainly focused on local-file-sharing approach using proprietary applications. Limited research focused on using BIM as an online gaming platform to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Kumar et al [17] found importing BIM data directly into the game engine through a FBX file format to be the best workflow when aiming to transfer as much information as possible. Recent research recommends taking an intermediate step by importing BIM data to Autodesk 3DS Max ©, and then to the game engine [15,18] to overcome the reported inaccuracies related to distorted geometries, missing textures and the overall organization of the model hierarchy [13][14][15][16][17][18]. This proposed workflow can be seen as a routinized workaround as several researchers have tested and reported improvements to the process, and illustrates that a digital BIM-gaming integration is affordable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kumar et al [17] found importing BIM data directly into the game engine through a FBX file format to be the best workflow when aiming to transfer as much information as possible. Recent research recommends taking an intermediate step by importing BIM data to Autodesk 3DS Max ©, and then to the game engine [15,18] to overcome the reported inaccuracies related to distorted geometries, missing textures and the overall organization of the model hierarchy [13][14][15][16][17][18]. This proposed workflow can be seen as a routinized workaround as several researchers have tested and reported improvements to the process, and illustrates that a digital BIM-gaming integration is affordable.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges are due to different data structures and ways to store information within each technology. Distorted geometries, missing textures or faults related to the overall organization of the model hierarchy are examples of frequently reported interoperability issues [13][14][15][16][17][18]. Thus BIM data is not always correctly interpreted by game engines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Yang [20] proposed a learning tool to educate non-experts about energy-related design and decision-making; Shen et al [21] developed a web-based 3D game project to demonstrate the process of using BIM to create an interactive 3D on-line training environment focusing on the energy commissioning of heating, ventilation and air-conditioning (HVAC) systems; Rüppel and Schatz [22] designed a new serious gaming approach based on BIM for the exploration of the effect of building condition on human behavior during the evacuation process; Dib and Adamo-Villani [23] described the development and initial evaluation of a serious game for learning sustainable building design principles and practices; and Liu et al [24,25] developed a framework to build a human behavior library through a BIM based cloud gaming environment and to solicit and collect human egress behavior data from a larger pool of human beings.…”
Section: Bim-based Architectural Visualization and Integration With Gmentioning
confidence: 99%